2009
DOI: 10.1016/j.cellimm.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 and antigen dose differentially regulate perforin- and FasL-mediated cytolytic activity in antigen specific CD4+ T cells

Abstract: CD4 T cell effectors can promote survival against lethal influenza virus via perforin mediated cytolytic mechanisms, however; our understanding of how naïve CD4 cells differentiate into class II restricted killers remains obscure. To address this, TCR Tg CD4 cells were activated in vitro and examined for their ability to lyse target cells. We found that cytokine polarized CD4 T cell effectors displayed cytolytic activity with the hierarchy Th0>Th1>Th2. Further, IL-4 inhibited the generation of cytotoxic CD4 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 70 publications
(96 reference statements)
6
139
1
Order By: Relevance
“…Consistent with other studies, our results demonstrated that CD4 + T cells elicited antiviral lytic T cell response apart from helper mechanisms (35) that is essential for retaining long-term immune control (36,37). Cytolytic CD4 + T cells are important in many chronic infections, such as EBV, HIV, and HCMV (38). In addition, the CD4 + T cells elicited a profound response to NEWTinfected iDC.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with other studies, our results demonstrated that CD4 + T cells elicited antiviral lytic T cell response apart from helper mechanisms (35) that is essential for retaining long-term immune control (36,37). Cytolytic CD4 + T cells are important in many chronic infections, such as EBV, HIV, and HCMV (38). In addition, the CD4 + T cells elicited a profound response to NEWTinfected iDC.…”
Section: Discussionsupporting
confidence: 79%
“…It is worth noting that the in vitro cytotoxicity of the T-cell product for UPN-02, which consisted primarily of CD4 ϩ T cells, was equivalent to that of the other patients with CD8 ϩ -predominant products. Robust cytolytic activity can be acquired by CD4 ϩ cells cultured in vitro with IL-2 44 and has been observed with ex vivo cultured CD4 ϩ CAR T cells in clinical trials as well. 2 As with our previous study, we found no evidence of cellular or humoral immune responses against the infused cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that effector CD4 ؉ T cells can directly kill target cells by employing the cytolytic molecules Gzmb and perforin (13,16). We examined the expression of Gzmb in CD4 ؉ T cells during influenza A/PR8 virus infection.…”
Section: T-bet-and Blimp-1-dependent Development Of Cd4mentioning
confidence: 99%
“…Thus, understanding the cellular and molecular mechanisms regulating the development of these cells is of considerable significance with respect to viral infections, cancer, and autoimmunity. Currently, interleukin-2 (IL-2) signaling, low antigen dose, as well as OX40 and 41BB stimulation (13)(14)(15), have been suggested to promote the development of CD4 ؉ T cells with cytotoxic potential. However, the physiological signals in vivo and the downstream signaling pathways, as well as the underlying transcription factors regulating the development of these CD4 ϩ T cells remain undefined.…”
Section: N Aive Cd4mentioning
confidence: 99%